PERSUASIVE LANGUAGE IN ADVERTISEMENT DISCOURSES (BUSINESS ADVERTORIAL ANALYSIS) - Rizkia Amirotul Kubro; Imam Suyitno (Jurusan Sastra Indonesia, 2019)
The goal of this research is to determine the persuasive language in the business advertorial advertisements in online daily news which it has seen from persuasive language forms (included diction and expressions), persuasive techniques, and discourse structures. The design of the study is using a qualitative approach and used a content analysis study. The research findings indicate that persuasive language forms and persuasive techniques used to give profit, explain product competition, and establish product quality. Discourse structures in business advertorial advertisements have two major patterns, namely conventional and unconventional.